Legal Knowledge and Information Systems. - Lodder, A. R. (IOS Press, 2007)
This volume contains the Proceedings of the Nineteenth JURIX Conference on Legal Knowledge and Information Systems (JURIX 2006). The large number of submissions shows that the interdisciplinary community is still growing and active. This volume again covers a broad range of topics. Argumentation is central to legal reasoning and therefore it is no surprise that researchers have focused on computational theories of argumentation. In this book four papers are dedicated to this topic. Typical to the legal field is the use of written knowledge sources, especially legal sources. These have been sub.